High-performance gamma-based titanium-aluminum alloy and additive manufacturing method thereof

By mixing titanium-aluminum alloy powder with aluminum powder of matching particle size, and using selective laser melting additive manufacturing and hot isostatic pressing, the problem of forming complex structural parts from titanium-aluminum alloys has been solved, and γ-based titanium-aluminum alloys with excellent high-temperature tensile strength and oxidation resistance have been achieved, which are suitable for aerospace components.

CN121017577AActive Publication Date: 2025-11-28NINGBO ZHONGKE XIANGLONG LIGHTWEIGHT TECH CO LTD +2

Patent Information

Application Number
CN202511558543.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-29
Publication Date
2025-11-28
Estimated Expiration
2045-10-29

AI Technical Summary

Technical Problem

Existing technologies are difficult to effectively form high-performance titanium-aluminum intermetallic compounds, especially in complex structural parts and under high-temperature conditions, where forming defects and performance instability exist.

Method used

By using a mixture of titanium-aluminum alloy powder and aluminum powder with matched particle size, and through selective laser melting additive manufacturing (SLM) combined with hot isostatic pressing (HIP) and solution heat treatment, the process parameters and composition design are optimized to ensure the formation and stability of the γ phase and eliminate printing defects.

Benefits of technology

A γ-based titanium-aluminum alloy with excellent high-temperature tensile strength and oxidation resistance has been developed, which can be formed into complex thin-walled structural parts to meet the high-performance requirements of aerospace components.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a high-performance gamma-based titanium-aluminum alloy and an additive manufacturing method thereof. The additive manufacturing method comprises the following steps: selecting proper titanium-aluminum alloy powder and aluminum powder; mixing the titanium-aluminum alloy powder with aluminum powder to obtain mixed powder; the mixed powder is fed into SLM equipment, printing is carried out in the inert gas protection atmosphere, a printing-state alloy blank with the density larger than or equal to 97% is obtained, and at the moment, a mixed structure of a titanium-aluminum intermetallic compound and an aluminum phase is preliminarily formed in the blank; the printed alloy blank is placed in hot isostatic pressing equipment to be subjected to hot isostatic pressing treatment; and the alloy subjected to hot isostatic pressing treatment is subjected to solid solution heat treatment. According to the method, the synergistic problem of SLM forming-defect elimination-phase regulation and control is broken through, the process chain is optimized, the gamma-phase dominated high performance is guaranteed, meanwhile, the process simplicity and cost advantages are achieved, the method is the optimal scheme for solving the titanium-aluminum additive manufacturing bottleneck at present, and the use requirement of the low-pressure turbine blade of the aero-engine is met.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the technical field of titanium-aluminum alloy manufacturing, and particularly relates to a high-performance gamma-based titanium-aluminum alloy and an additive manufacturing method thereof. BACKGROUND

[0002] Selective Laser Melting (SLM) additive manufacturing technology, as an important branch of metal additive manufacturing, has great application potential in high-end manufacturing fields such as aerospace, automobile manufacturing and biomedical engineering, due to its ability to near-net shape complex structural parts, high material utilization rate and precise size control. This technology realizes the direct manufacturing of three-dimensional solid parts by selectively melting metal powder layer by layer with a high-energy laser beam, which can break through the limitations of traditional forging and casting processes in complex structure forming and provide a new technical path for the rapid preparation of high-performance metal components.

[0003] Titanium-aluminum intermetallics-based titanium-aluminum alloys have become an ideal candidate material for replacing traditional nickel-based high-temperature alloys and reducing the weight of hot-end components such as aerospace engines, due to their low density (about 3.9-4.7 g / cm 3 For example, in the components such as low-pressure turbine blades and high-pressure compressor blades of an aero-engine, the application of titanium-aluminum intermetallic parts can significantly reduce the overall weight of the engine, improve the thrust-to-weight ratio, and thus improve the fuel efficiency and maneuverability of the aircraft.

[0004] However, titanium-aluminum intermetallics have inherent defects such as high room temperature brittleness and poor plasticity, and its traditional forming processes (such as casting and forging) face many challenges: casting is prone to defects such as porosity and segregation, which leads to fluctuations in mechanical properties; forging needs to be carried out at high temperatures, which is energy-consuming and requires harsh conditions for the mold, especially for complex structural parts. Therefore, applying laser selective melting additive manufacturing technology to the forming of titanium-aluminum intermetallics has become an important exploration direction to solve the problem of preparing complex structures.

[0005] Chinese invention patent, publication number CN117488144A discloses a kind of additive manufacturing high-performance aluminum-titanium metal composite material and its preparation method, its core is aluminum matrix composite material: with aluminum alloy (85~98wt%) as matrix, titanium alloy powder (2~15wt%) as reinforcing phase, the essence is through titanium alloy modification aluminum alloy organization (such as refinement equiaxed crystal, form core-shell structure), final performance relies on the strengthening of aluminum matrix. Its application scene is more inclined to medium-low temperature structural parts (such as general machinery, automobile lightweight parts), not suitable for aerospace high-temperature parts (such as engine blades, combustion chamber). In addition, the patent only uses titanium alloy as the passive reinforcing phase of aluminum matrix, does not actively control the phase composition of titanium-aluminum intermetallic compound, and does not design subsequent processing according to the characteristics of titanium-aluminum intermetallic compound. SUMMARY

[0006] To solve the problems in the prior art, the purpose of the present application is to provide a high-performance γ-based titanium-aluminum alloy and an additive manufacturing method thereof.

[0007] To achieve the above-mentioned purposes and achieve the above-mentioned technical effects, the technical solutions adopted by the present application are as follows: An additive manufacturing method of a high-performance γ-based titanium-aluminum alloy, comprising the following steps: 1) selecting suitable titanium-aluminum alloy powder and aluminum powder; 2) mixing powder: mixing the titanium-aluminum alloy powder and the aluminum powder to obtain a mixed powder; 3) laser melting additive manufacturing: feeding the mixed powder into an SLM device and printing under an inert gas protective atmosphere to obtain a printed alloy blank with a density ≥97%, at which time a mixed structure of titanium-aluminum intermetallic compound and aluminum phase is initially formed in the blank; 4) placing the printed alloy blank in a hot isostatic pressing device for hot isostatic pressing treatment; 5) solid solution heat treatment of the alloy after hot isostatic pressing.

[0008] Further, in step 1), the titanium-aluminum alloy powder is spherical titanium-aluminum alloy powder with a particle size of 25~53μm.

[0009] Further, in step 1), the aluminum powder is spherical aluminum powder with a particle size of 18~45μm and a purity ≥99.7%.

[0010] Further, in step 2), the mass ratio of the titanium-aluminum alloy powder to the aluminum powder is 2.15~2.45:1.

[0011] Further, in step 2), the titanium-aluminum alloy powder and the aluminum powder are mixed in a planetary ball mill, and the ball milling parameters are set as follows: ball-to-material ratio 6:1~9:1, rotation speed 220~280r / min, ball milling time 2.5~3.5h, and argon gas protective atmosphere is used to avoid oxidation of the powder.

[0012] Further, in step 3), the process parameters are set as follows: laser power 280~320W, scanning speed 1000~1300mm / s, layer thickness 35~45μm, and scanning interval 90~110μm.

[0013] Further, in step 3), the scanning strategy is as follows: bidirectional cross scanning is adopted, the rotation between layers is 67° to reduce anisotropy, and the edge scanning speed is reduced by 20% to reduce spheroidization effect.

[0014] Further, in step 4), the printed alloy blank is placed in a hot isostatic pressing device, and is kept at a temperature of 1100~1250℃ and a pressure of 100~200MPa for 2~4h, and then is cooled to room temperature in the furnace.

[0015] Further, in step 5), the alloy after hot isostatic pressing is heated to 900~1050℃, kept for 2~4h, and then is rapidly cooled by oil cooling.

[0016] The application further discloses a high-performance gamma-based titanium-aluminum alloy prepared by the additive manufacturing method.

[0017] Compared with the prior art, the application has the following beneficial effects: 1) The application discloses that Ti 85% and Al 15% (initial atomic ratio ≈5.67:1) titanium-aluminum alloy powder is selected instead of traditional TiAl pre-alloy powder, and a combination of "high-Ti base powder + additional pure Al powder" is used to reserve a precise component space for the generation of the gamma phase (TiAl); the component of the traditional pre-alloy powder (such as Ti-48Al-2Cr-2Nb) is fixed, and the phase ratio cannot be adjusted according to the SLM rapid solidification characteristics, while the high-Ti base of the titanium-aluminum alloy powder can flexibly adapt to the subsequent Al powder supplement amount, thereby avoiding the problem of TiAl3 brittle phase caused by local Al enrichment when pure Ti powder and pure Al powder are directly mixed; the Ti and Al content fluctuation in the titanium-aluminum alloy powder is controlled within ±0.5wt%, so that after the titanium-aluminum alloy powder is mixed with the Al powder at a mass ratio of 2.15~2.45:1, the adjusted overall Ti and Al atomic ratio of the system is stabilized at 1.05~1.1:1 (the atomic ratio range in which the gamma phase stably exists is 0.8~1.2:1), and the problem of "gamma phase + alpha2 phase ratio out of control" caused by component segregation in the SLM process is solved; 2) Functional component design of aluminum powder, considering phase regulation and process adaptability: directional control of purity and impurities: aluminum powder purity ≥ 99.7%, and strictly limit Fe ≤ 0.1wt%, Si ≤ 0.05wt%, which is different from the conventional industrial pure aluminum powder (Fe ≤ 0.2wt%, Si ≤ 0.1wt%), avoiding the formation of low melting point eutectic phase (such as Ti6Al4Fe, Ti5Si3) at the grain boundary of γ-TiAl phase, resulting in softening of the grain boundary at high temperature; the present application reduces the impurity content, so that the bonding strength of the γ phase grain boundary is increased by more than 15%, and the high temperature tensile strength at 800℃ is increased by 30~50MPa compared with the conventional aluminum powder formulation; Particle size gradient matching design: aluminum powder particle size 18~45μm (D50=32μm) and titanium-aluminum alloy powder 25~53μm (D50=38μm) form a gradient ratio, rather than equal particle size mixing, small particle size aluminum powder can fill the voids between large particle size titanium-aluminum alloy powder, so that the loose bulk density of the mixed powder is increased from 2.5g / cm 3 to 2.8g / cm 3 , the SLM powder layer density is increased to more than 92% (the conventional mixed powder has a powder layer density of ≤88%), reducing the un-melted defects caused by large gaps between the powders during printing; 3) Dynamic component compensation design of mixed powder, creative solution to SLM burning loss; aluminum powder burning loss compensation mechanism; during SLM process, aluminum is prone to burning loss of about 1.5~2wt% due to its low boiling point (2467℃), traditional formulations do not consider this problem, resulting in insufficient Al content in the final component, high proportion of α2 phase (Ti3Al) (more than 15%), and decreased plasticity, while the creativity of the present application lies in: in the basic mass ratio of 2.15~2.45:1, additional 0.3~0.5wt% aluminum powder is added to form a burning loss compensation allowance, ensuring that the actual Al content of the printed component still meets the demand for γ phase dominance (α2 phase proportion controlled at 5~8%); 4) Process innovation: breaking through the coordination problem of "SLM forming-defect elimination-phase regulation", optimizing the process chain, ensuring high performance with γ phase dominance, and having the advantages of simple process and cost advantage, which is the optimal solution to solve the bottleneck of titanium-aluminum additive manufacturing at present; 5) Through the coordination of formulation and process, the present application realizes the high temperature tensile strength at 800℃ ≥400MPa, and the endurance life ≥100 hours (100MPa load), meeting the requirements of low pressure turbine blades of aircraft engines (800℃ tensile strength ≥350MPa, endurance life ≥50h); the oxidation weight gain of conventional Ti-48Al-2Cr-2Nb alloy is ≥0.3mg / cm 2 , while the oxidation weight gain of the present application after oxidation at 800℃ for 100h is ≤0.1mg / cm 2 , forming a dense The protective layer solves the industry problem of poor high-temperature oxidation resistance of γ-TiAl alloys; 6) Traditional casting of γ-TiAl alloys cannot form complex thin-walled structures with a wall thickness of ≤3mm, and is prone to incomplete casting and cracks; This invention, through the synergy of SLM process and formulation, can form thin-walled blades with a wall thickness of 1.5mm (minimum fillet radius of 0.5mm), and after forming, there are no cracks or porosity defects (defect rate ≤0.1%), and the dimensional accuracy of the components reaches ±0.1mm, meeting the near-net-shape forming requirements of complex aerospace structures; Creative principle: High flowability of the mixed powder (bulk density ≥ 2.8 g / cm³) 3 The precise energy control of SLM (Self-Drying Molding Machine) avoids deformation and cracking caused by heat accumulation during the printing of thin-walled parts, while traditional formulations suffer from poor powder flowability (bulk density ≤ 2.5 g / cm³). 3 The pass rate for forming thin-walled parts is only 50%, but this invention can increase it to over 95%. Detailed Implementation

[0018] The present invention will now be described in detail so that its advantages and features can be more easily understood by those skilled in the art, thereby providing a clearer and more explicit definition of the scope of protection of the present invention.

[0019] The following provides a brief overview of one or more aspects to offer a basic understanding of them. This overview is not an exhaustive summary of all conceived aspects, nor is it intended to identify key or decisive elements of all aspects, nor to define the scope of any or all aspects. Its sole purpose is to present some concepts of one or more aspects in a simplified form to prepare for the more detailed descriptions that follow.

[0020] This invention discloses an additive manufacturing method for high-performance γ-based titanium-aluminum alloys, comprising the following steps: 1) Material selection: Titanium-aluminum alloy powder: Spherical titanium-aluminum alloy powder with a particle size range of 25~53μm is selected. Its main components are titanium and aluminum, and the titanium-aluminum atomic ratio can be pre-controlled according to the target γ (TiAl, atomic ratio 1:1) phase composition. This powder must meet the requirements of high sphericity (≥98%, and satellite powder content ≤0.5wt%), low oxygen content (≤0.12wt%), nitrogen content (≤0.05wt%), hydrogen content (≤0.0015wt%), and narrow particle size distribution to ensure powder flowability (loose packing density ≥2.8g / cm³). 3 And the uniformity of melting during the SLM forming process; Aluminum powder: Select the particle size range of 18~45μm spherical aluminum powder, purity ≥99.7%, also need to have high sphericity (≥98%) and low impurity content (oxygen content ≤0.08wt%, Fe ≤0.1wt%, Si ≤0.05wt%), its role is to adjust the system aluminum content by mixing powder, to provide the composition basis for the subsequent γ (TiAl) phase formation, reduce the porosity between the powder layer, improve the melting uniformity, and relieve the thermal stress during SLM forming.

[0021] 2) Mixing powder: the titanium aluminum alloy powder and aluminum powder are placed in a planetary ball mill according to a specific mass ratio (2.15~2.45:1) to mix, and the mixed powder is obtained, the ball milling parameters are set as: ball-to-material ratio 6:1~9:1, rotation speed 220~280r / min, ball milling time 2.5~3.5h, and argon gas (purity ≥99.999%, dew point ≤-40℃) is used as the protective atmosphere, which can avoid the adsorption of moisture in the powder during ball milling, reduce the introduction of O and H elements caused by the decomposition of H2O during SLM, and experiments show that when the dew point is ≤-40℃, the oxygen content of the mixed powder increases by only 0.02wt% (the conventional argon protection increases by 0.05~0.08wt%), which avoids the formation of TiO2 inclusions (which will reduce the elongation by 20~30%) by γ phase oxidation. Through ball milling, the titanium aluminum alloy powder and aluminum powder are uniformly dispersed, and at the same time, the mechanical force is used to refine the surface morphology of the powder, promote the interface bonding in the subsequent SLM process; If the rotation speed is too high and the time is too long, the titanium aluminum alloy powder will be excessively cold-welded to form agglomerates of more than 100μm, which cannot be melted during SLM, and if the rotation speed is too low and the time is too short, the mixing uniformity is poor, and Ti-rich areas appear after printing, forming α2 brittle phase. Therefore, by optimizing the rotation speed and time, the mixed powder achieves macroscopic uniformity (composition deviation ≤0.3wt%) and microscopic interface activation (a plastic deformation layer of 5~10nm is formed on the surface of the titanium aluminum alloy powder), which avoids agglomeration and promotes the Ti-Al diffusion reaction during SLM through interface mechanical activation, and the γ phase generation rate is increased to more than 90% (the conventional ball milling formula has a γ phase generation rate of ≤75%).

[0022] 3) Laser melting additive manufacturing: the mixed powder is sent into the powder cylinder of the SLM equipment, and printing is carried out under the protection of inert gas (such as argon) atmosphere (oxygen content ≤0.01%), and the core process parameters are as follows: laser power 280~320W, scanning speed 1000~1300mm / s, corresponding energy density is relatively low (70~100J / mm 3 ), if the energy density is too high, it will cause local overheating, grain coarsening (γ phase grain ≥50μm) and thermal stress cracks, layer thickness 35~45μm, scanning spacing 90~110μm; the scanning strategy is: bidirectional cross scanning is adopted, the interlayer rotation is 67° to reduce anisotropy, the edge scanning speed is reduced by 20%, and the density is increased to 120J / mm3 , reduce the spheroidization effect; Through the above parameter control, the powder is fully melted and rapidly solidified to form fine crystals (gamma phase grains 10~20 μm), and a printed alloy blank with a density ≥97% is obtained, at this time, a mixed structure of titanium-aluminum intermetallic compounds and aluminum phases is preliminarily formed in the blank; The edge of the SLM component is prone to spheroidization effect (surface roughness Ra≥15 μm) due to fast heat dissipation and insufficient melting, and the present application makes the edge melt more fully through high energy density, and the surface roughness is reduced to Ra≤8 μm, which can meet the surface precision requirement (Ra≤10 μm) of the aero-engine blade without subsequent machining, and the machining allowance is reduced by more than 30%.

[0023] 4) Hot isostatic pressing (HIP) treatment: the printed alloy blank is placed in a hot isostatic pressing device, and is kept at a temperature of 1100~1250℃ and a pressure of 100~200MPa for 2~4h, and then is cooled to room temperature in the furnace. This step can eliminate pores, micro-cracks and other defects generated during printing through low temperature and high pressure, improve the density of the blank to ≥99%, and promote atomic diffusion to lay the organizational foundation for the formation of gamma phase, and the growth rate of gamma phase grains is controlled to ≤20%, realizing the cooperation of defect elimination and grain refinement.

[0024] 5) Solution heat treatment: the alloy after hot isostatic pressing treatment is heated to 900~1050℃, kept for 2~4h, and then rapidly cooled by oil cooling, and the cooling rate is ≥50℃ / min, and finally a microstructure with a gamma (TiAl) phase as a matrix and a small amount of alpha2 (Ti3Al) phase uniformly distributed is obtained, realizing the synergistic optimization of strength and plasticity; In this step, rapid oil cooling can inhibit the transformation of gamma phase to alpha2 phase, so that the proportion of alpha2 phase is stably controlled at 5~8%, and the proportion of alpha2 phase is 12~15% by conventional air cooling; at the same time, the solution temperature of 900~1000℃ can make the solute atoms (such as Ti and Al) in the gamma phase uniformly distributed, avoid the brittle fracture caused by local alpha2 phase enrichment, and the room temperature elongation is improved by 0.8~1.2 percentage points compared with the conventional air cooling process.

[0025] The application further discloses a high-performance gamma-based titanium-aluminum alloy prepared by the additive manufacturing method.

[0026] Example 1

[0027] An additive manufacturing method of a high-performance gamma-based titanium-aluminum alloy, comprising the following steps: 1) Material selection: Titanium-aluminum alloy powder: spherical titanium-aluminum alloy powder with a particle size range of 25-53 μm (D10=25 μm, D50=38 μm, D90=53 μm) is selected, the main components of which are titanium (Ti 84.3285%) and aluminum (Al 15%), and the Ti and Al content fluctuation is controlled within ±0.5wt%, the sphericity is 98%, the satellite powder content is 0.5wt%, the oxygen content is 0.12wt%, the nitrogen content is 0.05wt%, and the hydrogen content is 0.0015wt%; Aluminum powder: spherical aluminum powder with a particle size range of 18-45 μm (D50=32 μm) is selected, the purity is 99.85%, the iron content is 0.1wt%, and the silicon content is 0.05wt%; 2) Powder mixing: titanium-aluminum alloy powder and aluminum powder are placed in a planetary ball mill according to a specific mass ratio (2.3:1) for mixing, considering that about 1.5-2wt% of aluminum is burned during the SLM process, 0.4wt% of aluminum powder is additionally added, the mixed powder is obtained, the ball milling parameters are set as follows: ball-to-powder ratio 8:1, rotation speed 250 r / min, ball milling time 3h, and argon gas (purity≥99.999%, dew point≤-40℃) protective atmosphere is used to avoid powder adsorbing moisture during ball milling and reduce the introduction of O and H elements caused by H2O decomposition during SLM. Experiments show that when the dew point is≤-40℃, the oxygen content of the mixed powder increases by only 0.02wt% (the conventional argon protection increases by 0.05-0.08wt%), which avoids the formation of TiO2 inclusions (which reduces the elongation by 20-30%) caused by γ-phase oxidation. The uniform dispersion of titanium-aluminum alloy powder and aluminum powder is realized through ball milling, and the surface morphology of the powder is refined by mechanical force to promote the interface bonding during the subsequent SLM process; 3) Laser melting additive manufacturing: the mixed powder is sent into the powder cylinder of the SLM equipment, and printing is carried out under the protection of inert gas (argon) atmosphere (oxygen content≤0.01%), the core process parameters are as follows: laser power 300W, scanning speed 1200mm / s, corresponding energy density is relatively low (80J / mm 3 ), layer thickness 40 μm, scanning interval 100 μm; the scanning strategy is: bidirectional cross scanning is used, the interlayer rotation is 67° to reduce anisotropy, and the edge scanning speed is reduced by 20% to reduce spheroidization effect; Through the above parameter control, full melting and rapid solidification of the powder are realized, and a printed alloy blank with a density of 97.5% and a surface roughness Ra≤8 μm is obtained, at this time, a mixed structure of titanium-aluminum intermetallic compound and aluminum phase is preliminarily formed in the blank; 4) Hot Isostatic Pressing (HIP) Treatment: The printed alloy billet is placed in a hot isostatic pressing apparatus and held at 1180℃ and 160MPa for 3 hours, then cooled to room temperature with the furnace. This step, through low temperature and high pressure, can eliminate defects such as porosity and microcracks generated during the printing process, increase the density of the billet to ≥99%, and promote atomic diffusion, laying the microstructure basis for the formation of the γ phase. The γ phase grain growth rate is controlled at ≤20%, achieving a synergistic effect of defect elimination and grain refinement.

[0028] 5) Solution heat treatment: The alloy after hot isostatic pressing is heated to 980℃ and held for 2.5h. Then, it is rapidly cooled by oil cooling at a rate of 50℃ / min. Finally, a microstructure with γ (TiAl) phase as the matrix and a small amount of α2 (Ti3Al) phase uniformly distributed is obtained, which achieves synergistic optimization of strength and plasticity.

[0029] This embodiment also discloses a high-performance γ-based titanium-aluminum alloy prepared by an additive manufacturing method.

[0030] Example 2

[0031] An additive manufacturing method for a high-performance γ-based titanium-aluminum alloy includes the following steps: 1) Material selection: Titanium-aluminum alloy powder: Spherical titanium-aluminum alloy powder with a particle size range of 28~50μm (D10=28μm, D50=40μm, D90=50μm) is selected. Aluminum powder: Spherical aluminum powder with a particle size range of 20~42μm (D50=30μm) is selected; 2) Powder mixing: Titanium-aluminum alloy powder and aluminum powder are mixed in a planetary ball mill at a specific mass ratio (2.25:1). Considering the loss of about 1.5~2wt% of aluminum during the SLM process, an additional 0.35wt% of aluminum powder is added to obtain mixed powder. The ball milling parameters are set as follows: ball-to-material ratio 7.5:1, rotation speed 230r / min, ball milling time 3.2h, and argon gas (purity ≥99.999%, dew point ≤-40℃) protective atmosphere is used. 3) Laser Melting Additive Manufacturing: The mixed powder is fed into the powder cylinder of the SLM equipment, and printing is performed under an inert gas (argon) protective atmosphere (oxygen content ≤0.01%). The core process parameters are as follows: laser power 290W, scanning speed 1100mm / s, corresponding to a relatively low energy density (75J / mm). 3 The layer thickness is 38 μm and the scanning interval is 95 μm. The scanning strategy is as follows: bidirectional cross scanning is adopted, interlayer rotation is 67° to reduce anisotropy, and the edge scanning speed is reduced by 20% to reduce sphericity. By controlling the above parameters, the powder is fully melted and rapidly solidified to obtain a printed alloy blank with a density of 97.8%. At this time, a mixed structure of titanium-aluminum intermetallic compound and aluminum phase is initially formed in the blank. For complex structural parts with a wall thickness of 2mm, the forming accuracy reaches ±0.08mm. 4) Hot Isostatic Pressing (HIP) treatment: The printed alloy billet is placed in a hot isostatic pressing equipment and held at 1160℃ and 170MPa for 3.2h, and then cooled to room temperature with the furnace. 5) Solution heat treatment: The alloy after hot isostatic pressing is heated to 960℃ and held for 2.8h. Then, it is rapidly cooled by oil cooling at a rate of 50℃ / min. Finally, a microstructure with γ (TiAl) phase as the matrix and a small amount of α2 (Ti3Al) phase uniformly distributed is obtained, which achieves synergistic optimization of strength and plasticity.

[0032] This embodiment also discloses a high-performance γ-based titanium-aluminum alloy prepared by an additive manufacturing method.

[0033] The rest is the same as in Example 1.

[0034] The high-temperature performance of the high-performance γ-based titanium-aluminum alloys obtained in Examples 1-2 was tested, and the results are as follows: Example 1: The tensile strength at 800℃ is 420MPa, and the creep rupture life reaches 110h under a 100MPa load; the weight gain due to oxidation at 800℃ / 100h is only 0.08mg / cm³. 2 Anisotropy: The ratio of horizontal to vertical tensile strength is 0.96.

[0035] Example 2: The tensile strength at 800℃ is 410MPa, and the creep rupture life reaches 105h under a 100MPa load; the oxidation weight gain at 800℃ / 100h is only 0.09mg / cm³. 2 Complex structure forming effect: A complex combustion chamber structure with multiple cooling film holes (0.8 mm in diameter) and a wall thickness of 2 mm was successfully prepared. There were no internal defects such as cracks and pores, and the defect rate was ≤0.08%.

[0036] Compared with existing technologies, the present invention has at least the following technical effects: Compared to traditional casting processes, which are unable to form complex thin-walled structures with a wall thickness of ≤3mm and are prone to problems such as incomplete filling and cracking, this invention successfully fabricates structural parts with a wall thickness of 2mm and tiny cooling film pores by optimizing powder properties (such as particle size matching and high purity) and SLM process parameters (such as energy density and scanning strategies optimized for complex structures). The forming qualification rate has been increased from 50% in traditional processes to 96%. Compared to other additive manufacturing cases of γ-TiAl alloys, some existing additive manufacturing processes do not consider powder burn-off compensation, leading to component composition deviations and unstable performance. This invention, through precise burn-off compensation design, ensures stable component composition and good performance consistency. Furthermore, in terms of forming accuracy and defect control for complex structures, this case, through refined process parameters, outperforms most similar studies, providing a more reliable solution for manufacturing complex structural components of gas turbine combustors.

[0037] Any parts or structures not specifically described in this invention can be made using existing technologies or products, and will not be elaborated upon here.

[0038] The above description is merely an embodiment of the present invention and does not limit the patent scope of the present invention. Any equivalent structural or procedural transformations made based on the content of the present invention specification, or direct or indirect applications in other related technical fields, are similarly included within the patent protection scope of the present invention.

Claims

1. A method of additive manufacturing of high performance gamma based titanium aluminide alloys, characterized in that, The method comprises the following steps: 1) selecting titanium-aluminum alloy powder and aluminum powder; 2) mixing the powder: mixing the titanium-aluminum alloy powder and the aluminum powder to obtain mixed powder; 3) laser melting additive manufacturing: feeding the mixed powder into an SLM device, printing under an inert gas protective atmosphere to obtain a printed alloy blank with a density of ≥97%, at this time, a mixed structure of titanium-aluminum intermetallic compounds and aluminum phases is preliminarily formed in the blank; 4) placing the printed alloy blank in a hot isostatic pressing device for hot isostatic pressing treatment; 5) solid solution heat treatment of the alloy after hot isostatic pressing.

2. The method of additive manufacturing of high performance gamma based titanium aluminide alloy as claimed in claim 1, wherein, In step 1), the titanium-aluminum alloy powder is spherical titanium-aluminum alloy powder with a particle size of 25-53 μm.

3. The method of additive manufacturing of high performance gamma based titanium aluminide alloy as claimed in claim 1, wherein, In step 1), the aluminum powder is spherical aluminum powder with a particle size of 18-45 μm and a purity of ≥99.7%.

4. The method of additive manufacturing of high performance gamma based titanium aluminide alloy as claimed in claim 1 wherein, In step 2), the mass ratio of the titanium-aluminum alloy powder to the aluminum powder is 2.15-2.45:

1.

5. The method of additive manufacturing of high performance gamma based titanium aluminide alloy as claimed in claim 1, wherein, In step 2), the titanium-aluminum alloy powder and the aluminum powder are mixed in a planetary ball mill, and the ball milling parameters are set as follows: ball-to-material ratio of 6:1-9:1, rotation speed of 220-280 r / min, ball milling time of 2.5-3.5 h, and argon protective atmosphere is used to avoid oxidation of the powder.

6. The method of additive manufacturing of high performance gamma based titanium aluminide alloy as claimed in claim 1 wherein, In step 3), the process parameters are set as follows: laser power of 280-320 W, scanning speed of 1000-1300 mm / s, layer thickness of 35-45 μm, and scanning spacing of 90-110 μm.

7. The method of additive manufacturing of high performance gamma based titanium aluminide alloy as claimed in claim 1 wherein, In step 3), the scanning strategy is as follows: bidirectional cross scanning is used, the rotation between layers is 67° to reduce anisotropy, and the edge scanning speed is reduced by 20% to reduce spheroidization effect.

8. The method of additive manufacturing of high performance gamma based titanium aluminide alloy as claimed in claim 1 wherein, In step 4), the printed alloy blank is placed in a hot isostatic pressing device, and is kept at a temperature of 1100-1250 °C and a pressure of 100-200 MPa for 2-4 h, and then is cooled to room temperature in the furnace.

9. The method of additive manufacturing of high performance gamma based titanium aluminide alloy as claimed in claim 1 wherein, In step 5), the alloy after hot isostatic pressing is heated to 900-1050 °C, kept for 2-4 h, and then is rapidly cooled by oil cooling.

10. A high-performance γ-based titanium-aluminum alloy prepared by the additive manufacturing method of the high-performance γ-based titanium-aluminum alloy according to any one of claims 1-9.

Citation Information

Patent Citations

  • Additive manufacturing high-performance aluminum-titanium metal composite material and preparation method thereof

    CN117488144A

  • Additive manufacturing method for high-performance titanium-aluminum alloy with fine-grain fully lamellar structure

    CN115261658A

  • Electron beam selective melting TiAl alloy and preparation method

    CN118513565A

  • Method for processing quasi-continuous net-shaped reinforced titanium-based composite material thin-wall structure through cold spraying additive-hot pressing equal material

    CN119640252A

  • Layered regulation and control method for microstructure of additive manufacturing titanium-aluminum alloy

    CN120060689A

Cited By

  • TiAl alloy and additive manufacturing composite process preparation method and application thereof

    CN121696411A